Catalytic oxidation of cinnamyl alcohol using Au–Ag nanotubes investigated by surface-enhanced Raman spectroscopy1. Issue 18 (14th May 2015) - Costa, Jean Claudio Santos; Corio, Paola; Rossi, Liane Marcia
<x xml:space="preserve">Abstract</x> Au–Ag NTs were used as both catalysts and SERS active substrates to investigate the catalytic oxidation of a molecule without surface-anchoring groups.